Beyond anosmia: olfactory dysfunction as a common denominator in neurodegenerative and neurodevelopmental disorders - Chen, Yu-Nan; Kostka, Johanna Katharina (Frontiers in Neuroscience, 2024)
Olfactory dysfunction has emerged as a hallmark feature shared among several neurological conditions, including both neurodevelopmental and neurodegenerative disorders. While diseases of both categories have been extensively studied for decades, their association with olfaction has only recently gained attention. Olfactory deficits often manifest already during prodromal stages of these diseases, yet it remains unclear whether common pathophysiological changes along olfactory pathways cause such impairments. Here we probe into the intricate relationship between olfactory dysfunction and neurodegenerative and neurodevelopmental disorders, shedding light on their commonalities and underlying mechanisms. We begin by providing a brief overview of the olfactory circuit and its connections to higher-associated brain areas. Additionally, we discuss olfactory deficits in these disorders, focusing on potential common mechanisms that may contribute to olfactory dysfunction across both types of disorders. We further debate whether olfactory deficits contribute to the disease propagation or are simply an epiphenomenon. We conclude by emphasizing the significance of olfactory function as a potential pre-clinical diagnostic tool to identify individuals with neurological disorders that offers the opportunity for preventive intervention before other symptoms manifest.